Association of cytologic grade of anal “Pap” smears with viral loads of human papillomavirus types 16, 18, and 52 detected in the same specimens from men who have sex with men - Utaiwan Utaipat (2018)
© 2016 Elsevier B.V. Background Human papilloma virus (HPV) load has been linked to cellular abnormalities of the uterine cervix, and proposed as predictors of HPV persistence and progression of dysplasia to cervical cancer. However, the association of HPV viral load and anal dysplasia and cancer has not been as thoroughly investigated. Objectives To examine the association of the viral loads of high-risk HPV types 16, 18, and 52, with the cytologic severity grading in anal-swab specimens of MSM with and without HIV-1 co-infection. Study design A cross-sectional study recruited 200 MSM in northern Thailand from July 2012 to January 2013. Real-time qPCR amplified portion of the HPV E6E7 gene, as well as the human β-globin gene to validate adequacy of the anal specimens and to normalize interpatient viral-load comparisons. Genotyping by linear-array assay identified and distinguished types 16, 18, and 52. Results HPV-16, and -18 viral loads increased with respect to the abnormality of the cytologic diagnoses (p < 0.05 for HPV-16, p < 0.01 for HPV-18). HIV-1 positivity was associated with higher HPV-18 viral load (p = 0.006). HPV-16 viral loads ≥102.24copies per 5000 anal cells, and HPV-18 loads ≥103.15, were independently associated with abnormal cytology on logistic regression (p = 0.022, p = 0.041, respectively). Positive predictive values were 85.2% (23/27) and 80.0% (44/55) for the high viral load of a particular HPV-16 and the combined HPV-16, -18 and -52 types, respectively. Conclusions High viral loads of HPV types 16 and 18 appear to be associated with anal cytologic abnormalities. The clinical utility of HPV viral loads to predict risk for anal cancer remains to be determined by a larger prospective cohort with sufficient frequency of high-grade dysplasia.